Genetically Engineered Mouse Models of Pituitary Tumors - Cano, David A.; Soto-Moreno, Alfonso; Leal-Cerro, Alfonso (Frontiers in Oncology, 2014)
Animal models constitute valuable tools for investigating the pathogenesis of cancer as well as for preclinical testing of novel therapeutics approaches. However, the pathogenic mechanisms of pituitary tumor formation remain poorly understood, particularly in sporadic adenomas, thus making it a challenge to model pituitary tumors in mice. Nevertheless, genetically engineered mouse models (GEMMs) of pituitary tumors have provided important insight into pituitary tumor biology. In this paper, we review various GEMMs of pituitary tumors, highlighting their contributions and limitations, and discuss opportunities for research in the field.